Cyberwarfare : an introduction to information-age conflict - Porche, Isaac, 1968- (Artech House intelligence and information operations series., 2020)
Conflict in cyberspace is becoming more prevalent in all public and private sectors and is of concern on many levels. As a result, knowledge of the topic is becoming essential across most disciplines. This book reviews and explains the technologies that underlie offensive and defensive cyber operations, which are practiced by a range of cyber actors including state actors, criminal enterprises, activists, and individuals. It explains the processes and technologies that enable the full spectrum of cyber operations. Readers will learn how to use basic tools for cyber security and pen-testing, and also be able to quantitatively assess cyber risk to systems and environments and discern and categorize malicious activity. The book provides key concepts of information age conflict technical basics/fundamentals needed to understand more specific remedies and activities associated with all aspects of cyber operations. It explains techniques associated with offensive cyber operations, with careful distinctions made between cyber ISR, cyber exploitation, and cyber attack. It explores defensive cyber operations and includes case studies that provide practical information, making this book useful for both novice and advanced information warfare practitioners.--